PENGARUH KEPEMIMPINAN TERHADAP KINERJA DOSEN DI PERGURUAN TINGGI - Purwanto S.K. (Jurnal Manajemen., 2015)
The Competitiveness of a nation is determined by the quality of higher education, especially in the technological and innovation. Improving the quality of higher education related to the performance lecturer in the areas of education, research and publications, and community service. Lecturer performance improvement requires the competence and commitment of university leadership. A leader in university must make a good organizational climate especially education and training that engagement and developed in its members. This study aims to determine the impact of leadership on the performance of lecturers. The study was conducted at state and private universitiesin Jakarta with a sample of 60 lecturers. The results showed that leadership in higher education that can improve the performance of the lecturer. Variables significant are able to provide exemplary leadership, make decisions quickly, giving delegates the authority, and a high level of optimism.